2006
DOI: 10.1002/ajh.20716
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent acute myeloid leukemia with inv(16)(p13.1q22) and chronic lymphocytic leukemia: Molecular evidence of two separate diseases

Abstract: Acute myeloid leukemia (AML) occurring concurrently with or after untreated chronic lymphocytic leukemia (CLL) is rare. We report a case of a 59-year-old man who was evaluated for anemia, thrombocytopenia, and leukocytosis with circulating blasts. On the basis of the morphology and immunophenotyping results, a preliminary diagnosis of chronic myelomonocytic leukemia with concurrent CLL was considered. Subsequently, cytogenetic analysis of the leukemic blood specimen revealed inv(16)(p13.1q22) with secondary tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 33 publications
0
10
0
2
Order By: Relevance
“…Our cases support the idea that AML and CLL might demonstrate two separate disease processes, which is CLL originates from abnormal CD5+CD19 positive lymphoid clone whereas AML originates from myeloid from CD34, CD117, CD13, CD33, and MPO positive myeloid clone. Lu CM et al showed that in a patient AML and CLL developed from different clones [13]. We only showed immunophenotypic features of AML and CLL were different.…”
Section: Discussionmentioning
confidence: 52%
“…Our cases support the idea that AML and CLL might demonstrate two separate disease processes, which is CLL originates from abnormal CD5+CD19 positive lymphoid clone whereas AML originates from myeloid from CD34, CD117, CD13, CD33, and MPO positive myeloid clone. Lu CM et al showed that in a patient AML and CLL developed from different clones [13]. We only showed immunophenotypic features of AML and CLL were different.…”
Section: Discussionmentioning
confidence: 52%
“…Therapy-related acute monoblastic leukemia (M5) in CLL, as in the present case, has rarely been reported [Lavabre-Bertrand et al 1989]. Our review of previously published cases demonstrates that AML and CLL may be diagnosed concurrently or after a variable latency period (<2-13 years) [Bracey et al 1989;Robertson et al 1994;Mateu et al 1997;Meloni et al 2000;Molero et al 2001;Lam et al 2005;Lu et al 2006;Hatoum et al 2007;Park et al 2009]. Rarely, the development of AML may not manifest with peripheral circulating blasts [Robertson et al 1994].…”
Section: Discussionmentioning
confidence: 58%
“…The present patient did not have any high-risk genetic mutations, however, overt DIC may reflect the aggressive disease manifestation. A few cases with normal karyotype or good-risk cytogenetics such as t(15;17) or inv(16) have also been reported [Molero et al 2001;Lu et al 2006;Hatoum et al 2007]. Unlike the majority of patients, who have poor outcomes [Bracey et al 1989;Robertson et al 1994;Mateu et al 1997], patients with good-risk cytogenetics may have good outcomes [Molero et al 2001;Lu et al 2006;Hatoum et al 2007;Park et al 2009].…”
Section: Discussionmentioning
confidence: 99%
“…18,19 Postoje i hipoteze da ove bolesti nastaju istodobno iz istog klona matične stanice ili je, pak, riječ o dva odvojena procesa. 7,15,[19][20][21][22][23][24] Istodobno prisutni KLL i MDS dijagnostički su izazov. U bolesnika s KLL-om i citopenijom treba pomišljati i na istodobno prisutan MDS.…”
Section: Raspravaunclassified